THE STUDY OF THE CROSS-BORDER TRANSPORTATION OF GRAIN CARGO BY ROAD AND RAIL - Didusenko, V. V.; Kravchenko, M. A.; Zolotarov, M. A.; Prokhorchenko, H. O. (Systems and Technologies, 2022)
The article examines the cross-border transportation of grain cargo by road and rail. In order to conduct a detailed analysis, the organization of grain transportation from Ukraine to Germany by rail and road on the route Lukiv, Ukraine – Rostock, Germany is studied. The article analyzes the time of cargo transportation on the route with a breakdown by type of operation: – time under cargo and customs operations; downtime under technical operations; and time in motion. The route and running speeds of grain transportation by road and rail are calculated. The main «bottlenecks" in the technology of cross-border transportation of grain cargo from Ukraine are identified. For a comprehensive assessment of the advantages and disadvantages of using rail or road transport for the transportation of grain cargo, the cost of the route under study was calculated. A comparative analysis of the cost of grain transportation when choosing different transportation schemes is carried out. The dependence of the cost of transportation on the distance is constructed. The areas of economic feasibility of using road transport in comparison with rail transport are found. A comparative analysis of the tariff systems for long-distance grain transportation in the export traffic of various railway carriers with options for transportation by road has shown the competitiveness of the road tariff in the transportation area up to 130 km. Based on the dependencies of the tariff for the transportation of 1 ton of grain by railroad carriers and road transport on the transportation distance calculated according to public tariffs, the author identified zones of economic feasibility of using road transport. The first zone of expediency of using road transport compared to the lowest railroad tariff of DB Cargo Polska S.A. is within 50 km. The second zone according to the tariff of JSC Ukrzaliznytsia is up to 94 km. The third zone according to PKP Cargo S.A. is up to 130 km. The article concludes that cross-border transportation of grain cargoes by road and rail from Ukraine to Germany is efficient.